The Loch Ness Model : Can ICTs Bridge the Accountability Gap? - Gigler, Bjorn-Soren; Bailur, Savita; Anand, Nicole (World Bank, Washington, DC, 2014)
Can information and communication technologies (ICTs) empower through participation, transparency, and accountability and if so, under which conditions? Theory and practice demonstrate that technologies can empower citizens to hold governments and international donors accountable, but true accountability will only result from recognizing the gap between supply (governments, international donors, service providers) and demand (citizens, civil society organizations, communities) and considering how to bridge it from both sides. ICT-enabled initiatives have contributed to shrinking this accountability gap, yet in many cases, it remains open. In this paper, the authors develop a framework for analyzing how technologies can accelerate efforts to close the gap, which the authors call the loch ness model. The authors offer reasons why the gap remains open and put forth recommendations for closing it.